Elevated fecal calprotectin as a biomarker of sepsis in preterm neonates: A cross-sectional study - Latif, Lory Iswanto; Febriani, Andi Dwi Bahagia; Alasiry, Ema; Baso, Aidah Juliaty A; Machmoed, Hadia Angriani; Jusli (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Fecal Calprotectin (FC) is used to determine the presence of infection in the intestine. Some studies have found high concentrations in sepsis infants with necrotizing enterocolitis but have not compared those with sepsis and without sepsis. This study evaluated the difference between FC levels in sepsis and without sepsis. Methods: A cross-sectional study was conducted. Infants aged 0 to 14 days with gestational age 28-36 weeks consist of the patient who was diagnosed with sepsis and without sepsis based on the European Medicines Agency (EMA) score. Clinical and biochemical data were collected from medical records. Fecal samples were analyzed for FC levels using the ELISA method. Results: We enrolled 88 neonates consisting of 40 neonates with sepsis and 48 neonates without sepsis. FC was higher in the sepsis infants’ group than in healthy infants (P<0.05). Multivariate analysis showed no variables significantly determining the FC level in sepsis infants. Conclusions: Preterm neonates with sepsis have higher FC levels than preterm neonates without sepsis.